Dietary supplementation of Nile tilapia (Oreochromis niloticus) with β-glucan and/or Bacillus coagulans: Synergistic impacts on performance, immune responses, redox status and expression of some related genes - Fath El-Bab, Ahmed F.; Majrashi, Kamlah A.; Sheikh, Huda M.; Shafi, Manal E.; El-Ratel, Ibrahim T.; Neamat-Allah, Ahmed N. F.; El-Raghi, Ali A.; Elazem, Amar Y. Abd; Abd-Elghany, Mohamed F.; Abdelnour, Sameh A.; Abduh, Maisa S.; Jaremko, Mariusz; et al. (Frontiers in Veterinary Science, 2022)
A 14-week feeding study was conducted to assess the effects of feed supplementation with prebiotics β-glucan (BG group) and/or probiotics Bacillus coagulans (BC group) on O. niloticus growth performance, body analysis, intestinal structure, immunological response, and antioxidant status. The fish were equally divided into six groups, as follows: fish group fed an un-supplemented diet served as a control group; the other fish groups were fed supplemented diets with 0.1 g β-glucan kg-1; 1 g Bacillus coagulans kg-1; 2 g Bacillus coagulans kg-1; 0.1 g β-glucan combined with 1 g Bacillus coagulans kg-1;0.1 g β-glucan combined with 2 g Bacillus coagulans kg-1. The findings revealed that supplementing Bacillus coagulans and the β-glucan mixture improved growth performance and feed efficiency parameters (RGR and SGR) more than the other groups. The fish flesh analysis revealed increased crude protein and dry matter content and lower lipid and ash levels in the BG and BC supplemented groups than in the Control group. On the other hand, β-glucan and Bacillus coagulans supplementation significantly boosted antioxidant activity and immunological responses in serum as determined by CAT, MDA, lysozyme, and phagocytic activity. Dietary β-glucan and B. subtilis supplementation remarkedly enhanced anterior intestine villus histomorphometry characteristics. Furthermore, Bacillus coagulans, alone or in combination with β-glucan, could reduce HSP70 and IL-1β gene expression while increasing IL-8 and GH gene expression. According to the findings, Bacillus coagulans and/or BG increased growth performance by increasing gut health and morphology. Furthermore, β-glucan and Bacillus coagulans supplementation enhanced Tilapia's body composition, immunological responses, and antioxidant status.